Peran Fraud Triangle dalam Mendeteksi Financial Statement Fraud di Perusahaan Perbankan ASEAN - Yuwono, Yuliana Pertiwi; Marlina, Maria Assumpta Evi (E-Jurnal Akuntansi, 2021)
This research aims to determine the effect of fraud triangle theory toward Financial statement fraud. Financial statement fraud is proxied by earnings management.  Population in this study is non-Islamic commercial banking companies listed on SGX, MYX, SET, PSE and IDX. The sampling technique used purposive sampling. The total sample in the study was 66 non-Islamic commercial banking companies. The data analysis method used is multiple linear regression. The research results proved that Financial targets and change of auditors had a positive effect on Financial statement fraud while external pressure had a negative effect on Financial statement fraud. Financial stability and ineffective monitoring had no effect on Financial statement fraud. This research can be used as a reference by investors, the public, government and users of other financial statement information in order to detect Financial statement fraud through the fraud triangle theory. Keywords: Financial statement fraud; Earnings Management; Fraud Triangle.